One-Step Chronoamperometric Synthesized Nitrogen-Doped Graphene Oxide as a Novel Anode for Sodium-Ion Battery with an Enhanced Electrochemical Performance - Almarzoge, Mohammedmustafa; Gencten, Metin; Ozsin, Gamzenur (WILEY-V C H VERLAG GMBH, 2025)
Sodium-ion batteries (NIBs) have gained significant attention in recent years due to the global abundance and cost-effectiveness of sodium, making them a promising alternative to lithium-based batteries. In this study, nitrogen-doped graphene oxide powders (NGO) have been prepared in one step by using chronoamperometric method and then have been used as anode materials for NIBs. The NGO powder surface is covalently doped by C-N formation. The synthesized powder had few layers (similar to 3 layers) with nanocrystalline domain size (L alpha) similar to 46 nm, and the number of sp(2) carbon rings was calculated to be similar to 18. The initial discharge capacity recorded 199.8 mAh g(-1) at 0.1 C rate. Besides, the capacity retention for long-term cycling of 100 cycles at 2 C rate was 91.78 %. The deduced diffusion coefficient from galvanostatic intermittent titration technique (GITT) and electrochemical impedance spectroscopy (EIS) measurements for NGO as anode in NIBs is in the range of 10(-11)-10(-12) cm(2) s(-1). The electrochemical performance was attributed to the enhanced d-spacing of NGO up to 6.8 degrees A and formation large number of defects.
Keywords: Sodium-ion battery; Graphene oxide; Nitrogen doping; Carbonaceous anode; Chronoamperometric method; TRANSMISSION ELECTRON-MICROSCOPY; OXYGEN REDUCTION REACTION; HARD CARBON; RAMAN-SPECTROSCOPY; CYCLE; ELECTROCATALYST; STABILITY; COMPOSITE; SODIATION; INSERTION; Electrochemistry